A escola vai ao museu: uma análise dos projetos educativos de três museus do Estado de São Paulo - Ogasawara, Renato Nonato (2019)
Analyzing the history of museums, we understand that this institution has played different roles over time, reaching its contemporary configurations as a space also dedicated to education. Studies on museum education propose different ways of performing the educational function. One of the educational elements offered is the educational sector: a set of programs and activities directed to the public of the museum. Among these audiences is the school. The partnership between museum and school is present in almost all educational works of the museums that have the educational sector. The performance of educational programs with schools has gained a relevant place in the access of students to the museums. This research sought to understand how the educational programs are structured in the proposals of each museum, with emphasis on the actions aimed at the school public. Initially, we present a historic about the museum and its transformation into an educational institution, and then the description and analysis of the basic documentation of this research, identifying educational concepts and actions aimed at the school public. Fifteen work plans and 15 annual results reports produced by the Social Organizations (OS) responsible for the management of the Pinacoteca do Estado, Catavento Cultural and Afro Brasil Museum, were analyzed, as well as the public policies for the area. This research intends to know how the different types of museums configure their educational activities and orient them to the school, observing the variability of proposals, concepts, objectives, justifications, number of students attended and educators training